A Prospective Experimental Study to Investigate the Peritoneal Adhesion Formation of Argon Plasma Coagulation (APC) Versus a Novel Aerosol Plasma in a Rat Model. (August 2014) - Kraemer, Bernhard; Rothmund, Ralf; Fischer, Klaus; Scharpf, Marcus; Smaxwil, Luisa; Enderle, Markus Dominik; Wallwiener, Christian; Neugebauer, Alexander
Background . This is a prospective, randomized, controlled, single-blinded study to investigate peritoneal adhesion formation of standard argon plasma coagulation (APC) versus aerosol plasma coagulation in a rat model. Methods . Bilateral lesions were created on the abdominal wall of 16 female Wistar rats with standard and aerosol plasma coagulation APC energy in a standard fashion. After 10 days, the rats were killed humanely to evaluate the peritoneal trauma sites. Adhesion incidence, quantity, and quality were scored 10 days postoperatively and studied histopathologically. Results . Average energy intake was 97.7 ± 3.1 J for APC and 93.8 ± 4.2 J for aerosol plasma coagulation. Incidence of adhesion formation was 74.2% for standard APC and 16.1% for aerosol plasma coagulation ( P < .0001). Standard APC mainly results in dense adhesions. Histological evaluation revealed no significant difference with regard to the average depth of lesions created by APC and aerosol plasma coagulation ( P = 0.21) at day 10; both groups showed an identical morphology of necrosis and granulation tissue formation. Conclusions . This study compares adhesion formation of standard APC versus aerosol plasma coagulation in a rat model. Standard APC produced significantly more adhesions. Aerosol plasma coagulation creates fewer adhesions, which are of lower grade, which seems to be achieved mainly by improved peritoneal conditioning in this animal model.